Translation Analysis toward Expressions Mitigating Speech Act of Criticizing in Harper Lee’s to Kill A Mockingbird and Go Set A Watchman - Luthfiyah Hanim Setyawati; Mangatur Rudolf Nababan; Djatmika Djatmika (Journal of English Language Teaching and Linguistics, 2018)
Using descriptive qualitative method, this paper aims to identify the forms of mitigation of criticizing speech acts in two novels entitled To Kill a Mockingbird and Go Set A Watchman, to identify translation technique used and to describe the quality of translation of expressions mitigating speech act of criticizing in those novels. Data used were linguistic units (words, phrases, clauses, or sentences) represented mitigation types of criticizing speech act. The findings indicate that there were two mitigation types of speech act criticizing, namely external and internal. Expressions mitigating speech act of criticizing from those novels mainly had an equivalent message in Source Text (ST). Translation techniques applied to translate mitigation forms in criticizing speech act imply the translator’s competence in conveying the message of Source Text. Thus, it will impact on shifting meaning or even level of politeness.